The mitten string - Rosner, Jennifer; Swarner, Kristina (New York : Random House, 2014)
Ruthie Tober's family is known for the beautiful, warm mittens they knit so when she and her mother meet a deaf woman and her baby and give them shelter, Ruthie decides to design very special mittens for them.
"A PJ Library Book Club selection"--Jkt. flap.
Keywords: Mittens -- Fiction; Deaf people -- Fiction; People with disabilities -- Fiction; Jews -- Fiction; Mittens -- Juvenile fiction; Deaf people -- Juvenile fiction; People with disabilities -- Juvenile fiction; Jews -- Juvenile fiction